B(C6F5)3‐Catalyzed E‐Selective Isomerization of Alkenes. Issue 63 (1st September 2022) - Kustiana, Betty A.; Elsherbeni, Salma A.; Linford‐Wood, Thomas G.; Melen, Rebecca L.; Grayson, Matthew N.; Morrill, Louis C.
Abstract: Herein, we report the B(C6 F5 )3 ‐catalyzed E ‐selective isomerization of alkenes. The transition‐metal‐free method is applicable across a diverse array of readily accessible substrates, giving access to a broad range of synthetically useful products containing versatile stereodefined internal alkenes. The reaction mechanism was investigated by using synthetic and computational methods. Abstract : Move along !: Herein, we report the B(C6 F5 )3 ‐catalyzed E ‐selective isomerization of alkenes. The transition‐metal‐free method is applicable across a diverse array of readily accessible substrates, accessing a broad range of synthetically useful products containing versatile stereodefined internal alkenes. Synthetic and computational mechanistic studies indicate that the isomerization proceeds along competing 1, 2‐hydride shift and hydride abstraction pathways.